Pengaruh Collaborative Strategic Reading (CSR) Terhadap Keterampilan Membaca Pemahaman Teks Cerita Fantasi Siswa Kelas VII SMP N 13 Padang - Naina Sucia Ningsih; Hafrison, Mohamad (Jurnal Pendidikan Tambusai, 2024)
This study aims to analyze the effect of collaborative strategic reading (CSR) on reading comprehension skills of fantasy story texts of seventh grade students of SMP N 13 Padang. This type of research is quantitative research with experimental method. The research design was one group pretest and posttest design. The population in this study were grade VII students of SMP N 13 Padang who were enrolled in the 2023-2024 school year as many as 286 students. The sample in this study was class VII.3 students totaling 32 people through purposive sampling technique. Based on the results of the study, it can be concluded that CSR has a significant effect on reading comprehension skills and CSR can be applied in learning reading comprehension skills of fantasy story texts of VII grade students of SMP N 13 Padang.